2019
DOI: 10.1097/sap.0000000000002058
|View full text |Cite
|
Sign up to set email alerts
|

The Keystone Island Perforator Flap in Reconstruction of Large Myelomeningocele Defects

Abstract: Background Reconstruction of the skin defect after myelomeningocele repair is a crucial step that influences the quality of the surgical outcome. Keystone perforator flap is an islanded fasciocutaneous flap based on random regional perforators, which is advanced to adjacent defects. It has become a reliable method of locoregional reconstruction in various body parts with minimum morbidity. The aim of this study was to evaluate our clinical experiences in using keystone perforator flaps as an altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 20 publications
2
33
1
Order By: Relevance
“…Eight previous studies have discussed the use of KDPIFs for meningomyelocele defect closure [15,[18][19][20][21][22][23][24]. All of those studies also demonstrated satisfactory experiences in using KDPIFs for meningomyelocele closure.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Eight previous studies have discussed the use of KDPIFs for meningomyelocele defect closure [15,[18][19][20][21][22][23][24]. All of those studies also demonstrated satisfactory experiences in using KDPIFs for meningomyelocele closure.…”
Section: Discussionmentioning
confidence: 93%
“…Among 28 patients who underwent rotation/advancement flap closures, Gursoy et al [27] noted an average operative time of 86.25 minutes for single flaps, 115.45 minutes for double flaps, and 170.38 minutes for four-flap closures. In previous studies using keystone flap closures for meningomyelocele, Gutman et al [15], Donaldson et al [18], Park et al [19], Hifny and Hamdan [24] reported average operative times of 223, 236, 225, and 86 minutes, respectively. Our study showed an average of 89.6 minutes, with 70.6 minutes on average for unilateral key- This series demonstrated that KDPIFs were successfully implemented as locoregional fasciocutaneous flaps in the reconstruction of large meningomyelocele defects.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We suggested that this practice is too conservative and may cause severe complications of perforator kinking and flap loss. 7 Multiple studies worked on assessing the reliability of only one artery perforator as lumbar artery perforators or intercostal artery perforators. In comparison to our study, we worked on freestyle perforator pattern that allows more choices for designing the flap donor marking.…”
Section: Discussionmentioning
confidence: 99%